A Case Study on the Control of Large Deformations in a Roadway Located in the Du’erping Coal Mine in China - Xiaojie Yang; Chaowen Hu; Jianhui Liang; Yubo Zhou; Guofeng Ni; Ruifeng Huang (Advances in Materials Science and Engineering)
The effective control of large roadway deformations has always been a focus and difficulty in the coal industry. At present, a “bolt + cable + mesh + shotcrete” combined support structure has been widely used in China to support roadways with large deformations, and this method has achieved some success. However, large roadway deformations supported by using the “bolt + cable + mesh + shotcrete” support structure still have a series of engineering problems. This paper describes a case study of large deformation control in a roadway surrounded with broken rock located in the Du’erping coal mine in the Shanxi Province of China. A new “shell + bolt + shotcrete” combined support structure is proposed to support the north wing main haulage roadway. Methods were adopted from theoretical analysis, numerical simulation, and similarity simulation experiments to design a reinforced shell within a vertical wall semicircular arch. Roadway convergence and surrounding rock stress were monitored on the site. The monitoring data showed that the new support structure successfully controlled a potentially large deformation of the roadway. This new combined support structure provides a helpful reference for the design and engineering of support structures to prevent large roadway deformations.